Developing an mHealth app for post-stroke upper limb rehabilitation: Feedback from US and Ethiopian rehabilitation clinicians. (June 2020) - Hughes, Charmayne Mary Lee; Padilla, Alejandra; Hintze, Amy; Raymundo, Tatiana Mariscal; Sera, Michael; Weidner, Sven; Ontiveros, Jonathan; Peng, Tony; Encarcion, Aaron; Cruz, Zeus A; Warner, Sam; Sany, Kedir; et al.
Stroke is the leading cause of adult disability worldwide, with 70 percent of survivors exhibiting residual impairments of the upper limb that require frequent in-person visits to rehabilitation clinic over several months. This study explored rehabilitation clinician's preferences for design features to be included in an mHealth-enabled app for post-stroke upper limb rehabilitation. Data were collected via online survey, sampling participants from Ethiopia ( n = 69) and the United States ( n = 75). Survey results indicated that Ethiopian and US rehabilitation clinicians have different opinions about the importance of design features that should be included in a stroke tele-rehabilitation system which are likely due to differences in culture, the availability of human and physical resources, and how the field of rehabilitation is organized and managed. Our results, thus, indicate that mHealth technologies must be tailored to the geographical and cultural context of the end users.